Impact evaluation of microfinance: A HEPM perspective - Kumar, Senthil; Aslam, Mohammad; Nawanir, Gusman; Moshood, Taofeeq Durojaye (EDP Sciences, 2023)
Microfinance services were primarily conceived for poverty alleviation and millions of borrowers have benefited across various countries. This study measures microfinance impact on borrowers from the following dimensions viz. enterprise, household, individual and security. The impact was measured by comparing the borrowers' poverty level before and after microfinance (within impact), and then with and without microfinance (between impact) using Household Economic Portfolio Model (HEPM). In general, it was observed that microfinance has had a favorable impact on borrowers. The income level of borrowers has increased after they availed the loan indicating that participant borrowers' financial position is better than that of the non-participant borrowers. The results confirm that both industry survival and growth are achievable thereby advocating that microfinance is a sustainable development tool in the current scenario. Hence, policymakers should continue framing strategies that are in favour of extending microfinance to micro-enterprises that are deprived of mainstream finance.